INCLUSIVE EDUCATION AND MODERN PEDAGOGICAL APPROACHES - Rahimjanova Muqaddas Dilmurod qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation This article explores the essence of inclusive education in modern pedagogy, emphasizing its significance in ensuring equal opportunities for all learners regardless of  their  physical,  social,  or  cognitive  differences.  The  study  also  examines  recent European  research  (2023–2025)  highlighting  innovative  teaching  methods,  teacher training,  and  policy  reforms  that  promote  inclusivity.  The  analysis  concludes  that inclusion is not only a social obligation but also a pedagogical strategy for sustainable development in education.